2014
DOI: 10.1021/jp4115173
|View full text |Cite
|
Sign up to set email alerts
|

Two-Color Surface Plasmon Polariton Enhanced Upconversion in NaYF4:Yb:Tm Nanoparticles on Au Nanopillar Arrays

Abstract: Spectroscopic imaging and time-resolved spectroscopy are used to study the surface plasmon polariton (SPP) enhanced infrared to visible upconversion luminescence from NaYF 4 :Tm:Yb nanoparticles embedded in polymethyl methylacrylate (PMMA) supported on Au nanopillar arrays. The arrays have a lattice resonance associated with the SPP near 980 nm, near-resonant with the peak absorption of the Yb 3+ ion, while a local surface plasmon resonance (LSPR) associated with the individual pillars is seen to enhance the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…The enhancement factor was 4.8 and 2.7 for green and red emissions, respectively. In addition, fine arrays of various noble metal nanostructures are efficient LSPR supporters, such as Au nanohole arrays, 305 Au surfaces, 306 Au nanopillar arrays, 307 and Au pyramid array. 308 …”
Section: Efficiency Enhancement Of Upconversion Emissionsmentioning
confidence: 99%
“…The enhancement factor was 4.8 and 2.7 for green and red emissions, respectively. In addition, fine arrays of various noble metal nanostructures are efficient LSPR supporters, such as Au nanohole arrays, 305 Au surfaces, 306 Au nanopillar arrays, 307 and Au pyramid array. 308 …”
Section: Efficiency Enhancement Of Upconversion Emissionsmentioning
confidence: 99%
“…2, 29, 40, 53 The mechanism for plasmonic-enhanced UC generation could involve enhanced near field at both the excitation and the emission. 19,21,53 In terms of contributions from the near field enhancement at the excitation wavelength (980 nm), the experiments consistently demonstrated an increase in UC emission when the laser excitation was polarized perpendicular to the slits (higher enhancement for xyx compared to the xxx configurations for the S300-slit sample, for instance -see Figure 6). Considering that the direct laser excitation of the emitters in the film is polarization-independent, the preferential emission for when the incident polarization is crossed relative to the slit direction suggests the generation of resonant near field modes at the excitation energy that contributes to the enhanced UC generation (SPP-type, according to FDTD).…”
Section: Resultsmentioning
confidence: 74%
“…17,18 It has been demonstrated that UC nanoparticles (UC NPs) luminescence can be enhanced when coupled to metallic nanostructures through resonant energy transfer (ET) involving surface plasmons (SPs). 17,[19][20][21] The capability of engineering SP-active nanostructures 22 (geometry and surrounding dielectric) for enhanced UC EOT might have a potential for applications in photonics, 23,24 and as sensitive single emitter detectors. [25][26][27][28] In this work, polarized EOT from UC emissions were experimentally demonstrated by using Au double-antenna nanoparticles (DA NPs) nested in nanoslits in thin gold films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sun et al 15 demonstrated that resonant surface plasmon polaritons (SPP) increase the rate of resonant energy transfer from Yb 3+ to Er 3+ ions by 6 fold on an organized pyramid gold substrate. Luu et al 16 also demonstrated SPP-enhanced infrared to visible upconversion luminescence from NaYF 4 :Tm:Yb nanoparticles embedded in polymethyl methylacrylate (PMMA) supported on Au nanopillar arrays. In this paper, we report on the controlled enhancement of UC emission from Yb 3+ -Er 3+ -Gd 3+ co-doped sodium yttrium fluoride (NaYF 4 :Yb/Er/Gd) nano-rods (UC NRs) in contact with gold nano-particle arrays (AuNPAs) of various periodicities.…”
Section: Introductionmentioning
confidence: 99%